Impact of Talent Retention Process on Employee Performance in Context of E-Commerce Industry of Bangladesh - Orion, Sharian Alam (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.